Pengaruh Work Motivation, Work Discipline dan Training Terhadap Employee Work Productivity - Kartini, Tri Mulyani; Etty Zuliawati Zed; Andrianto Prasetya Nugroho (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The success of a company is measured by how optimally it uses existing resources to achieve high productivity. This research aims to find out how much influence work motivation, work discipline and training have on the work productivity of PT employees. IEI. This type of research is quantitative research analyzed using statistics. The author is an employee of PT. IEI in the production operator section has a total population of 62 employees. The sample size uses a saturated sample by means of all members of the population being sampled. Data analysis used SPSS Version 25. This research resulted that the variables of work motivation, work discipline and training had a positive and simultaneous effect on the work productivity of PT employees. IEI. This is proven by the results of F calculated 59.747>2.76 (F calculated>F table) so that Ho4 is rejected and Ha4 is accepted. This means that there is a positive and significant influence between work motivation, work discipline and training simultaneously on the work productivity of PT employees. IEI.